Invectives against ignoramuses: Petrarch and the defense of humanist eloquence. Issue 2 (3rd April 2019) - Crick, Nathan
ABSTRACT: Francesco Petrarch was a pioneering figure not only in the study of the humanities, but also in the defense of the humanities. A prolific writer and avid reader of the classics, particularly of the historians, rhetoricians, and poets, Petrarch cleared the way for humanistic studies in an age dominated by rigid scholasticism. Not surprisingly, then, Petrarch also had to defend himself against attacks from establishment elites who condemned the new studies as useless distractions from the pursuit of knowledge, by which they meant the study of syllogisms. I argue in this essay that Petrarch's invectives against his detractors offer a unique and communicative defense of the humanities that does not rely on the traditional recourse to civic humanism, a tradition that arose only subsequent to Petrarch. In his understanding of humanism, the value of humanistic studies is found in their capacity to produce a combination of humility and love—humility by expanding the circumference of our experience and exposing the limitations of our knowledge, and love by the capacity to create unity out of division. Furthermore, Petrarch defines the enduring opponent of the humanities as the scholastic ignoramus, a character that endures today.